The Use of ‘Canva for Education’ and the Students’ Perceptions of Its Effectiveness in the Writing Procedure Text - Nabielah Luaily Fauziyah; J. Priyanto Widodo; Shierly Novalita Yappi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The aims of this study were to investigate the effectiveness of ‘Canva for Education’ and the students preceptions at MTs Sabilunnajah Prambon, Sidoarjo in the academic year 2020/2021. The research used a pre-experimental design with one group pre-test and posttest design. The treatment was conducted after the pre-test and before the post-test to the 48 students of class IX as the chosen sample of this study by using purposive sampling. The data instruments of this study were test and questionnaire. The research showed that ‘Canva for Education’ was effective in improving the students’ writing skills for procedure text. Then, based on the reliability of the questionnaire which was measured by SPSS 26, the Cronbach’s Alpha (α) statistical test showed the value was > 0.5. It could be concluded the variable perception of the students’ perceptions towards the use of ‘Canva for Education’ could be said to be reliable due to the Cronbach’s Alpha value is > 0.5, (p-value > 0.5 = 30.8 > 0.5). In other words, the students’ perception toward use of ‘Canva for Education’ in writing procedure text gave several impacts on improving their writing skills and they felt enthusiastic about learning by using ‘Canva for Education’.